On dual integral equations arising in problems of bending of anisotropic plates - B. D. Aggarwala; C. Nasim (International Journal of Mathematics and Mathematical Sciences)
In this paper we consider dual integral equations, which arise in boundary value problems of bending of anisotropic plates. The function involved in these equations is a linear combination of elementary function, which turns out to be a particular case of a class of Fourier kernels, [2]. The method used here for solving the equations is some what similar to the method used for solving dual integral equations of Titchmarsh type, [1].